When to call on an advantageous restart option - McGarvey, R. G. (Journal of Sports Analytics, 2018)
In an NCAA wrestling match, a coin toss occurs at the end of the first period. The coin toss winner can elect to begin the second period in a position he views as advantageous, in which case his opponent will determine the third period`s starting position, or the coin toss winner can defer his choice of starting position until the third period. This study examines two questions: What is the impact of the coin toss on the ultimate match outcome? Having won the coin toss, is it preferable to select the restart position in the second or the third period? The analysis finds that winning the coin toss does not, in itself, have a significant effect on the ultimate match outcome. However, the decision to defer has a considerable negative effect on the ultimate match outcome for the coin toss winner, with this effect being strongest when the match score is close at the end of the first period. This result is particularly surprising, given that wrestlers do not appear to demonstrate a uniform preference for deferring in close matches.